Relationships between 400-m hurdle performance and muscle cross-sectional area in trunk and thigh of take-off leg - Yoshimoto, T.; Chiba, Y.; Tamesue, D.; Ohnuma, H.; Yanaka, T.; Matsubayashi, T.; Sugisaki, N.; Iso, S.; Yamasaki, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
To elucidate the relationships between the muscle cross-sectional area of trunk and thigh and 400-m hurdle time in 400-m hurdler include bronze medalist in the world championships. Twelve young-adult male 400-m hurdlers took part in this study (height 175.4 ± 6.0 cm, body mass 67.9 ± 5.8 kg, 400-m hurdle time 47.89-55.41 s). Cross-sectional images from the origin to insertion of trunk and thigh muscles were obtained with via magnetic resonance imaging (MRI). Cross-sectional images from the origin to insertion of trunk and lower limb muscles were obtained with via magnetic resonance imaging (MRI). The absolute cross-sectional areas of each muscle were calculated as indices of muscularity using images. A stepwise multiple-regression analysis was performed to examine the association between the indices and 400-m hurdle time. A stepwise multiple-regression analysis produced an equation (adjusted R2 = .868) with the semitendinosus (ß = -0.611, P = .001), quadratus lumborum (ß = -0.300, P = .044) and adductor brevis(ß = -0.395, P = .014) as the explanatory variables. In conclusion, individual differences in 400-m hurdle performance can be explained by the semitendinosus, quadratus lumborum and adductor brevis.